THE PROFESSIONAL CONTEXT OF AUDIT VERSUS CORPORATION ON ACCOUNTING STUDENTS MORAL CONSIDERATION - Lidya Agustina; Christine Dwi KS; Setyo Tin (Universitas Hayam Wuruk Perbanas, 2012)
There have been some studies related to the moral consideration by the students of accountingor auditors as well. For that reason, some factors affecting the decision making by thisprofession is important to be studied. This study investigates whether the professional contextof accounting ethical dilemmas influences accounting students’ moral reasoning. In betweensubjects experiment, 110 accounting students from a private-accredited university in Bandung,responded to ethical dilemmas faced by either auditors or corporate accountants designedto measure their deliberative moral reasoning. As expected, students in the audit conditionexhibited significantly higher deliberative moral reasoning than students in the corporateaccounting condition. This result are consistent with accounting students having moreaudit based ethical knowledge structures which do not flexibly transfer to resolving ethicalissues in the corporate accounting context.